Relational Repair For A Wounded Planet: Restorative Justice In Environmental Criminal Jurisprudence (International Journal of Environmental Sciences, 2025)
The paper aims to examine how restorative justice can be made a crucial part of regulatory mix to enable present regulatory traditions to better repair and mend deleterious practices and prevent future environment degradation. Furthermore, it underscores how restorative justice can be applied in context of environmental harm. It takes into consideration a broader approach in conceptualising the meaning of regulation and view it as that large subset of governance which deliberately manoeuvres the flow of events. Therefore, the article focuses on ‘environmental restorative justice’ in place of ‘restorative environmental justice’ which entails all measures that can be employed in which restorative justice play a role in environmental protection of both restoration and care. In addition, it delves deeper into the aspect as to what would happen if restorative justice is infused with environmental stability and endeavours to examine how the impact of environmental restorative justice can be restored. Moreover, the article lays emphasis upon the more holistic integration and hybridisation of restorative justice into daily regulatory environmental practice so that it can penetrate into entire regulatory spectrum. It further aims to unravel the answers to pertinent questions that demands scholarly exploration— Who are the victims of environmental harm? Who should have a voice in restorative processes and what processes should be followed to decide this? What degree of offender acknowledgement of responsibility should be a prerequisite? What approaches are best, given that environmental offences are typically perpetrated by corporate entities? Who can speak on behalf of future or past generations ? And lastly, can restorative justice simultaneously safeguard communities and the environment?